Relationships among Gender, Physical Function and Surgical Procedure in Perioperative Gastrointestinal Cancer Patients - SAKURAI, Aiko; SHINOMIYA, Miho; MATSUZAWA, Masaru; SANO, Mitsuhiro; NONAKA, Yushi; KUSANO, Shusuke; KUBO, Akira; KUBOTA, Keisuke; NAKANO, Toru; HARA, Tsuyoshi; ICHIMURA, Shunsuke (Rigaku ryoho kagaku, 2012)
[Purpose] We investigated changes in perioperative gastrointestinal cancer patients’ physical function between before and after surgery, and the influence of gender and surgical procedure on the changes. [Subjects] The subjects were 50 perioperative gastrointestinal cancer patients, 27 males and 23 females with an average of 62.5±10.7 years, who were categorized by gender and two surgical procedures. [Method] We measured the 6-min walking distance (6MWD) of each patient before and after surgery, and calculated the postoperative distance as a percentage of the preoperative distance (%6MWD). [Results] For all patients, and by gender and surgical procedure, postoperative 6MWD significantly decreased. Further, for %6WMD we found main effects of both gender and surgical procedure. [Conclusion] A significant postoperative decrease in physical function of perioperative gastrointestinal cancer patients was found after surgery, and our results suggest the possibility that gender and surgical procedure are factors influencing the changes in postoperative physical function. We consider that information on gender and surgical procedure of perioperative gastrointestinal cancer patients is important information, because it indicates changes in postoperative physical function.